Pemahaman Pengelola Tentang Mudarabah dan Aplikasinya Dalam Lembaga Keuangan Mikro Syariah di Jawa Timur - Nurohman, Dede (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2022)
This paper aims to determine a comprehention of manager about a mudarabah contract and its application in Islamic microfinance institutions (LKMS). The research method used field research with a qualitative research type. The locus is in Kediri and its surroundings. The research subjects are LKMS managers. The method of sampling is purposive sampling. Data obtained from observations, documentation and in-depth interviews. The results showed that the understanding of the LKMS manager regarding the mudarabah contract had the same understanding as the fiqh literature as stated by the DSN-MUI fatwa. However, the application is different. With the fatwa, LKMS is more careful in distributing its funds. This is because LKMS only acts as an intermediary institution that represents depositors (savers customers) to ensure that the funds are safe and generate profit sharing.